Faktor Yang Berhubungan Dengan Hipertensi Pada Lansia di Puskesmas Sialang Buah Kec. Teluk Mengkudu Kab. Serdang Bedagai Tahun 2023 - Wahyuni Wahyuni; Zulkarnain Batubara; Rosmega Rosmega (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Hypertension is a non-communicable disease which is a very serious health problem today and is the biggest cause of stroke, both systolic and diastolic blood pressure. The incidence of hypertension is very high, especially in the elderly population. Objective: To determine the factors associated with the incidence of hypertension in the elderly at the Sialang Buah Health Center, Teluk Mengkudu District. Serdang Bedagai. Method: This research is an analytical study with a cross sectional design and a qualitative study was carried out using in-depth interviews. This research was conducted at the Sialang Buah Health Center from January to March 2023. The sample used was 125 people taken by accidental sampling. Univariate analysis is presented in the form of a frequency distribution table, while bivariate analysis uses the Chi-Square test with α = 0.05 and a confidence level of 95%. Results: there is a relationship between the level of salt consumption and the incidence of hypertension in the elderly (p = 0.025), there is a relationship between the level of consumption of fatty foods and the incidence of hypertension in the elderly (p = 0.010), there is no relationship between smoking habits and the incidence of hypertension in the elderly (p = 0.846), there is no relationship between exercise habits and the incidence of hypertension in the elderly (p = 0.179), there is no relationship between obesity and the incidence of hypertension in the elderly (p = 0.980), there is a relationship between stress levels and the incidence of hypertension in the elderly (p = 0.011), there is no relationship between socio-economic status and the incidence of hypertension in the elderly (p = 0.101). Conclusion: There is a relationship between salt intake habits and the incidence of hypertension in the elderly at the Sialang Buah Health Center. There is a relationship between the habit of consuming fatty foods and the incidence of hypertension in the elderly at the Sialang Buah Health Center. There is no relationship between smoking habits and the incidence of hypertension in the elderly at the Sialang Buah Health Center. There is no relationship between exercise habits and the incidence of hypertension in the elderly at the Sialang Buah Health Center. There is no relationship between obesity and the incidence of hypertension in the elderly at the Lubuk Minturun Cold Water Health Center. There is a relationship between stress and the incidence of hypertension in the elderly at the Sialang Buah Health Center. There is no relationship between socio-economic status and the incidence of hypertension in the elderly at the Sialang Buah Serdang Bedagai Health Center.